A Cytopathic Effect-Based Tissue Culture Method for HCoV-OC43 Titration Using TMPRSS2-Expressing VeroE6 Cells - Hirose, Ryohei (mSphere, 2021)
Human coronavirus (HCoV)-OC43 rarely shows a cytopathic effect (CPE) after infection of various cell lines, and the indirect immunoperoxidase assay (IPA), a relatively complex procedure, has long been used as an alternative assay. Because HCoV-OC43 uses cell-surface transmembrane protease serine 2 (TMPRSS2) for cell entry, VeroE6 cells expressing TMPRSS2 may show a clear CPE after HCoV-OC43 infection. The aim of this study was to construct a 50% tissue culture infectious dose (TCID(50)) assay for HCoV-OC43 based on CPE evaluation using VeroE6/TMPRSS2 cells. VeroE6/TMPRSS2 cells showed clear CPEs 3 to 4 days after low-titer HCoV-OC43 infection. Evaluation of viral kinetics indicated that the viral titer in the culture supernatant of VeroE6/TMPRSS2 cells in the early stages of infection was higher than that of other cells. In comparison, between the CPE-based and the IPA-based (i.e., the reference titer) methods, the titer measured with CPE evaluation 4 to 5 days after infection using VeroE6/TMPRSS2 cells showed a much smaller difference from the reference titer than that measured using other cells. Thus, the TCID(50) assay using CPE evaluation with VeroE6/TMPRSS2 cells provides the correct titer value and will greatly contribute to future research on HCoV-OC43. IMPORTANCE HCoV-OC43 rarely shows a cytopathic effect (CPE) in infected cell lines, and thus the plaque and TCID(50) assays by CPE observation are not applicable for titration; the indirect immunoperoxidase assay (IPA) is used instead. However, the IPA is relatively complex, time-consuming, costly, and not suitable for simultaneous titration of many samples. We developed a TCID(50) assay using CPE evaluation with TMPRSS2-expressing VeroE6/TMPRSS2 cells that provides the same accuracy as the conventional IPA-based viral titration and does not require any staining procedures using antibodies or substrates. This titration method will greatly contribute to future research on HCoV-OC43 by allowing simple, low-cost, and accurate titration of this virus.